Kebebasan dalam Kurikulum Prototype - Primanita Sholihah Rosmana; Sofyan Iskandar; Hilma Fauziah; Nadiyah Azzifah; Weby Khamelia (AS-SABIQUN, 2022)
The 2022 prototype curriculum is a curriculum implemented in the Driving School Program which refers to the Pancasila student profile to fortify students' abilities and character as an important part of implementing learning. The purpose of this study is to discuss freedom in the application of the 2022 prototype curriculum. This study uses a type of library research or literature study with a descriptive method. The purpose of implementing this type of research is to be able to provide a description of the findings of a literature study sourced from articles, journals, websites, or books related to the topic under study. The prototype curriculum is an educational program that is one of the choices (decisions) to make recovery in the implementation of learning. This curriculum structure contains teaching and learning that refers to achievement. The prototype curriculum that will be implemented by the Ministry of Education and Culture in the 2022/2023 academic year has very good goals, specifically requiring more dynamic and versatile progress by providing teachers with adaptability to carry out learning cycles that are for learning projects. To achieve this, the help and hard work of various groups should try to understand the superior teaching of the Indonesian language and develop it further.